Speech recognition and real-ear-measured amplification in hearing-aid users with various grades of hearing loss - Engler, Max; Digeser, Frank; Hoppe, Ulrich (International Journal of Audiology, 2024)
Objective: The relationship between aided speech recognition and hearing-aid (HA) amplification was investigated in a retrospective study. Design and study sample: Pure-tone thresholds, aided and unaided speech recognition and real-ear measurements of 635 ears in 374 HA users were reviewed. Ears were classified according to pure-tone average (PTA) and real-ear aided response (REAR) in relation to the targets of NAL-NL2 and DSL v5.0. Results: For DSL v5.0, compared with NAL-NL2, higher amplification was calculated almost consistently for input levels of 65 and 80 dB SPL. Speech-recognition scores were best when the REAR reached ±5 dB or exceeded 5 dB the DSL v5.0 target and were lowest when the REAR fell more than 5 dB below the NAL-NL2 target. Conclusions: The greatest impact of the REAR on speech recognition was observed at hearing losses between 50 and 80 dB HL. It was found that to optimise speech recognition and audibility for patients in this range HA fittings should target DSL v5.0 prescription values. For hearing losses below 50 dB HL, both NAL-NL2 and DSL v5.0 may be considered for HA fitting. However, for hearing losses above 80 dB HL, aided speech recognition is insufficient in most cases.
CRIS-Team Scopus Importer:2025-02-04
Keywords: DSL v5.0; hearing aid; NAL-NL2; real-ear measurement; speech recognition